2010
DOI: 10.4314/swj.v3i2.51799
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected metals in coal samples from Lafia-Obi and Chikila

Abstract: The concentration of iron, aluminum, chromium, magnesium cadmium, potassium, lead and copper in Lafia-Obi and Chikila coal samples were determined using atomic absorption spectroscopy (AAS). All the samples have comparable chromium and copper contents, while iron, aluminum, magnesium and potassium content vary to some extent. Metals concentrations in both Lafia-Obi and Chikila coal samples are within the limits allowed by the Federal Environmental Protection Agency (FEPA) except in Chikila (UBCJ-1) and Lafia-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The elemental composition and elemental ratios of the coal sample used in this study are listed in Table 5. The obtained values for C, N and H contents are within the range observed for various types of coal [66,62]. The C/N ratios of coal sample used in this study are higher than those reported for two south Brazilian coals [71].…”
Section: Proximate Analysis and Coal Qualitysupporting
confidence: 80%
See 3 more Smart Citations
“…The elemental composition and elemental ratios of the coal sample used in this study are listed in Table 5. The obtained values for C, N and H contents are within the range observed for various types of coal [66,62]. The C/N ratios of coal sample used in this study are higher than those reported for two south Brazilian coals [71].…”
Section: Proximate Analysis and Coal Qualitysupporting
confidence: 80%
“…The organic matter content calculated (OM %) was calculated from the carbon content by multiplying with a value of 1.7 ( Table 3). The derived organic matter content of the coal sample used in the present study is comparatively higher than Lafia-Obi coal (Jauro et al, 2008; Nasirudeen and Jauro, 2011).…”
Section: Proximate Analysis and Coal Qualitymentioning
confidence: 62%
See 2 more Smart Citations
“…It also presents the comprehensive data on the combustion characteristics, thermal behaviour, and degradation kinetics of CHK. Previous studies have examined the thermal analysis [21], pyrolysis and tar evaluation [22], mineralogical analysis [23] and organic geochemistry [14] of CHK in literature. To the best of authors' knowledge, there are limited data on the physico-chemical and thermokinetic fuel properties of Chikila coal, which this paper will address in detail.…”
Section: Introductionmentioning
confidence: 99%